Camel milk: a possible boon for type 1 diabetic patients - Agrawal, R. P.; Tantia, P.; Jain, S.; Agrawal, R.; Agrawal, V. (Cellular and Molecular Biology, 2013)
Poor nutrition in utero and in early life combined with over nutrition in later life may also play a role in epidemic of diabetes. The efficacy of camel milk consumption as an adjunct to routine diabetic management in type 1 diabetes is a approach showing new rays of hope to cope with this disorder by adding a food supplement with medicinal values. Research on the beneficial aspects of camel milk has been taking place in different corners of globe since last three decades. Continuous efforts to disclose the role of camel milk in diabetes has rendered it title of ‘white gold’. Biochemical studies has revealed the components e.g. insulin like protein, lactoferrin, immunoglobulins are responsible for imparting camel milk the scientific weightage. In parallel, epidemiological surveys stating low prevalence of diabetes in communities consuming camel milk clearly indicate towards its hopeful role in maintaining hyperglycemia. This article shades light on camel milk production, composition, characteristics as well as it expresses positive effect of camel milk on blood glucose level, insulin dose, beta cell function. This review also compiles various epidemiological studies carried out to bring forth utility of camel milk suggesting it as a useful food supplement or alternative therapy for type 1 diabetic patients.